2016
DOI: 10.1038/srep32612
|View full text |Cite
|
Sign up to set email alerts
|

Optimal search patterns in honeybee orientation flights are robust against emerging infectious diseases

Abstract: Lévy flights are scale-free (fractal) search patterns found in a wide range of animals. They can be an advantageous strategy promoting high encounter rates with rare cues that may indicate prey items, mating partners or navigational landmarks. The robustness of this behavioural strategy to ubiquitous threats to animal performance, such as pathogens, remains poorly understood. Using honeybees radar-tracked during their orientation flights in a novel landscape, we assess for the first time how two emerging infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 68 publications
0
27
0
Order By: Relevance
“…In addition, it would be possible that the disease agent itself benefited from an earlier onset of foraging if this promoted its horizontal transmission to other host colonies [62]. Indeed, in the case of DWV, a direct influence on the behaviour of its host is not unlikely, given that DWV particles have previously been found in the mushroom bodies-a key higher brain centre of these insects [31] (but see [34] for a study where no behavioural effects were found). Irrespective of these possible adaptive causes, it is clear that precocious foraging would have a major effect on colony well-being, as premature foraging partially depletes the nurse bee population [63] and disrupts various activities inside the hive [64][65][66], and rapid behavioural maturation has been shown to strongly accelerate the failure of stressed honeybee colonies [63].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, it would be possible that the disease agent itself benefited from an earlier onset of foraging if this promoted its horizontal transmission to other host colonies [62]. Indeed, in the case of DWV, a direct influence on the behaviour of its host is not unlikely, given that DWV particles have previously been found in the mushroom bodies-a key higher brain centre of these insects [31] (but see [34] for a study where no behavioural effects were found). Irrespective of these possible adaptive causes, it is clear that precocious foraging would have a major effect on colony well-being, as premature foraging partially depletes the nurse bee population [63] and disrupts various activities inside the hive [64][65][66], and rapid behavioural maturation has been shown to strongly accelerate the failure of stressed honeybee colonies [63].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, another tracking technology-harmonic radarwas recently used by one group to show that the emerging pathogen Nosema ceranae caused impaired homing behaviour in honeybees [45] and that Nosema infection also affected honeybee orientation flight behaviour [34]. The tracking method, however, was unable to reveal any correlation between DWV infection levels and orientation flight characteristic [34].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, empirical data indicate that for organisms the observed growth is often faster. Lévy walks (LWs) [1][2][3] and similar Lévy flights (LFs) [2,4,5] have been successfully applied to fit experimental data obtained from the movement patterns of many organisms and their cells, including T cells [6], microglia [7], starved slime mould (Dictyostelium discoideum) [8,9], swarming bacteria [10], fruit flies [11], honey bees [12,13], wandering albatrosses [14,15], marine predators [16], and humans [17][18][19] (also in human's gaze [20] and word association [21] trajectories). In many different random search scenarios, LWs and LFs have been shown to be advantageous over normal diffusion [22][23][24][25][26][27][28][29][30][31][32] and alternative superdiffusive models [33].…”
mentioning
confidence: 99%